PERSECUTION OF THE KURDISH PEOPLE ON BEHALF OF ANFAL - األستاذ المساعد الدكتور عادل عبد اهلل حمد (QALAAI ZANIST JOURNAL, 2021)
In recent years, the Anfal has become a terrifying word for the Kurdish individual. As soon as he hears of it, he remembers the days of the campaigns of repression and genocide that were directly targeted by the former Iraqi president Saddam Hussein. Although the Anfal is a Qur'anic term, and the verse of the verse is competent with the infidels, the Iraqi regime has committed it to achieve its objectives. This crime was conceived in a religious and Islamic way. It believed that obtaining financial, moral and political support was not enough. The leaders and peoples of the Islamic and Arab world that the Kurds infidels, mercenaries, apostates of Islam must be killed, and to drain their money and property, so as to justify his crimes, and get financial and military support. Regrettably, the tragedies suffered by the Kurdish people have been largely under the eyes of the world's nations, Four days after the bombing of the city of Halabja with chemical weapons, the Conference of the Union of Islamic States was held on 20/3/1988 and was attended by (42) Arab and Islamic countries. The conference discussed various issues and problems of Islamic and Arab countries such as Palestine, Afghanistan, Russia, and the Iraqi-Iranian war ... At the end of the conference, they accused Israel of persecuting the Palestinians ... but they did not find in the Halabja disaster what is most objectionable to them. The Western countries' position on the persecution of the Kurdish people was not more moderate than that of others. They rejected the Kurdish claims and calls that the international community had called for and the relief of the genocide that the Iraqi regime was subjected to. However, they considered these claims exaggerated. In fact, Kurdish opposition flags were unable to reach the truth of the plight of the Kurdish people to the international community, as confirmed by the Middle East Watch, after examining the documents and examining the evidence. The Kurds were not only indisputable, but in many cases they were below the level of the catastrophe that the Kurdish people were suffering from.